Pembinaan Ekstrakurikuler Futsal Untuk Meningkatkan Keterampilan Teknik Dasar Siswa SMP Negeri 44 Takengon - Alyadi S; Afrizal Afrizal; Imran Fadhil (Jurnal Pengabdian Pemersatu Bangsa, 2026)
This community service program aimed to improve the basic futsal skills of extracurricular students at SMP Negeri 44 Takengon through a structured coaching program. The activity involved 25 students participating in the school futsal extracurricular program and employed a participatory training approach combined with demonstrations, hands-on practice, mentoring, and evaluation. The coaching focused on developing fundamental futsal techniques, including passing, ball control, dribbling, and shooting, delivered progressively according to students' skill levels. Program evaluation was conducted through observations of students' technical performance before and after the training, complemented by participant response questionnaires. The results demonstrated significant improvements across all assessed technical skills. The average skill achievement increased from 62.25% before the program to 85.25% after its completion. In addition to technical improvement, students displayed greater enthusiasm, self-confidence, and active participation throughout the training sessions. The supervising teacher also gained practical knowledge of various training methods that can be sustainably implemented in extracurricular activities. This coaching program effectively enhanced the quality of futsal training at the school and can serve as a practical model for developing extracurricular sports programs to support students' athletic achievement